2018
DOI: 10.1136/jmedgenet-2017-104995
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for survival in patients with von Hippel-Lindau disease

Abstract: This largest VHL survival analysis indicates that onset age, family history, mutation type and first presenting symptom have an effect on the survival of patients with VHL disease, which is helpful to genetic counselling and clinical decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 29 publications
2
30
0
2
Order By: Relevance
“…However, conditions such as hereditary von Hippel-Lindau (VHL) disease or sporadic somatic inactivation of the VHL gene have been found to have a very close genetic association with ccRCC (4). The VHL gene was mapped at chromosome 3p25.3 (7,8), and the protein encoded by this gene (pVHL) was subsequently shown to form a complex with elongin C, elongin B and cullin-2 (9), which possesses ubiquitin ligase E3 activity. Upon its formation, this complex specifically recognizes the α subunits of two transcription factors, the hypoxia-inducible factors (HIFs) 1A and 2A, and directs them for degradation along the ubiquitin-proteasome pathway (8).…”
Section: Introductionmentioning
confidence: 99%
“…However, conditions such as hereditary von Hippel-Lindau (VHL) disease or sporadic somatic inactivation of the VHL gene have been found to have a very close genetic association with ccRCC (4). The VHL gene was mapped at chromosome 3p25.3 (7,8), and the protein encoded by this gene (pVHL) was subsequently shown to form a complex with elongin C, elongin B and cullin-2 (9), which possesses ubiquitin ligase E3 activity. Upon its formation, this complex specifically recognizes the α subunits of two transcription factors, the hypoxia-inducible factors (HIFs) 1A and 2A, and directs them for degradation along the ubiquitin-proteasome pathway (8).…”
Section: Introductionmentioning
confidence: 99%
“…Binderup et al (21) reported that the estimated mean life expectancy of a man with VHL is 67 years, whereas that for a woman with VHL is 60 years, which is higher than previously reported (49 years) (3). The results from our previous study demonstrated that the estimated median life expectancy is 62 years for Chinese patients with VHL disease (11). A deeper understanding of VHL syndrome, combined with the development of novel technology has therefore significantly improved the prognosis of affected patients.…”
Section: Discussionmentioning
confidence: 98%
“…It is therefore crucial to establish the optimal time point for surgery, in order to minimize the number of procedures, to preserve kidney integrity as long as possible and to improve patient quality of life. Medical advances and a deeper comprehension of VHL disease have allowed median survival time to increase from 49 to 62 years (3,11). A better understanding of the clinicopathological characteristics and prognosis of VHL-associated hereditary RCC may therefore aid clinicians in making more rational treatment decisions for patients with VHL.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, two asymptomatic VHL gene carriers (F2-III1, 5 years of age, p.N78S; F3-IV2, 21 years of age, p.R167Q) were identified via gene testing. Early diagnosis and genetic counseling, regular cancer screening and surveillance are therefore helpful for disease management and for the improvement of prognosis ( 40 ).…”
Section: Discussionmentioning
confidence: 99%